Dampak Pandemi Covid-19 Terhadap Laporan Laba Rugi Pada Bank Syariah - Rahayu Apriyanti (Neraca : Jurnal Akuntansi Terapan, 2022)
The study aims to determine the impact of the Covid-19 pandemic on profit and loss statements and Sharia Banks policies. This research uses documentation method with quantitative descriptive approach. The data used are in the form of profit and loss statements for BRI Sharia Bank, Mega Sharia Bank, and KB Bukopin Sharia Bank obtained from the Financial Services Authority (OJK). Then analyzed using One Sample TTest with SPSS version 23 program. The results of this study indicate that there is a significant difference before and during the Covid-19 pandemic at ROA <0,05 meaning that profitability is very adequate and profit exceeds the target. Sharia Banks policy has been adjusted by the OJK, namely implementing an economic stimulus policies related to restructuring financing based on POJK No.11/POJK.03/2020, and Sharia banks providing mobile banking facilities to facilitate transactions during the Covid-19 pandemic.